Investigation of Nursing Students' Viewpoints About Patient Safety and Medical Errors Witnessed in Clinical Practices - Emine Kır Biçer (Association of Nurse Managers, 2020)
INTRODUCTION: This study was planned to determine the medical errors that the nursing students witnessed, the medical errors they made in practice, and their opinions and thoughts about the culture of patient safety, of nursing students during clinical training. METHODS: A descriptive study was conducted with 246 nursing students who were studying and accepted to participate in the study at the School of Nursing in Hatay. As a data collecting instrument, 50 item questionnaire forms prepared by researchers. In the analysis of data frequency and percentage were used. RESULTS: During their clinical training, 90.2% participants previously heard that the concept of patient safety, 59.7% of students had witnessed medical errors, 24% of the participants made medical errors, 30.9% said that the received trainings were sufficient to prevent medical errors, 33.9% reported that they will report the errors made to the patient, 93.9 % of the errors were pharmaceutical errors. Nursing students were determined that the reasons for the occurrence of errors are mostly workers' training deficiencies and excessive workload. The students considered many patient safety areas as the nurses' responsibility. DISCUSSION AND CONCLUSION: In our study, it was determined that nursing students had awareness about patient safety, but lack of training in problem areas in patient safety, drug applications / drug management, reporting of medical errors, factors causing medical error, and responsibilities of health workers in patient safety.